2002
DOI: 10.1203/01.pdr.0000030885.86822.ad
|View full text |Cite
|
Sign up to set email alerts
|

Development of Coagulation Regulatory Proteins in the Fetal and Neonatal Lamb

Abstract: To investigate the development of coagulation regulatory proteins-protein C (PC), protein S (PS), and antithrombin (AT)-in relationship to the procoagulant protein factor X (FX), a chronically catheterized fetal ovine model was used. Infusion and sampling catheters were placed into pregnant ewes and their fetuses and maintained from mid-gestation. From a total of 110 fetuses, 17 lambs, and 63 ewes that were studied on one to 15 occasions, 212 fetal, 88 neonatal, and 157 maternal samples were obtained. Liver ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…We chose a fetal ovine (lamb) model to compare plasma recovery and elimination following infusion of replacement concentrates of these proteins in comparison to ewes. Previous studies of coagulation proteins in fetal and adult sheep (ewes) in our lab have shown good comparability with human (preterm and term neonate, child, adult) data [31][32][33] .…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…We chose a fetal ovine (lamb) model to compare plasma recovery and elimination following infusion of replacement concentrates of these proteins in comparison to ewes. Previous studies of coagulation proteins in fetal and adult sheep (ewes) in our lab have shown good comparability with human (preterm and term neonate, child, adult) data [31][32][33] .…”
Section: Introductionmentioning
confidence: 53%
“…We previously reported that ovine PC and AT can be detected in plasma of fetal lambs at 70 days of gestation (term gestation is 147 days) [33] . In that study, AT plasma concentrations increased linearly with gestational age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemostasis and hemostatic proteins differ between the fetus (and premature infant) and the term infant. [92][93][94] To date, there has been little consideration of how these differences might impact on the ultimate brain damage after hemorrhage. 5.…”
Section: Resultsmentioning
confidence: 99%